Pentingnya Pengembangan SDM - Nun Tufa (Fakultas Ekonomi dan Bisnis Islam, 2018)
Training and development is very important because tuntuntan from the world of a very complex organization, thus forcing an organization to conduct training and development so that employees are able to work in accordance with the expectations of the organization. Although many new employees are university graduates but in fact many of the employees are still confused with what they should do. In addition, capacity equalization is also a part of the objectives of human resource training and development.Human Resource Development is a form of effort to develop the quality of human resource capability through various process of planning method of education, training, and management of personnel or employees to achieve a satisfactory result.